Development and characterization of biodegradable film incorporated with turmeric oil: article / Muhammad Luqman Hakim Ahmad Tarmezie and Fariza Hamidon - Ahmad Tarmezie, Muhammad Luqman Hakim; Hamidon, Fariza (2017)
The study and experiment was conducted to evaluate the effect of different turmeric oil’s volume used (20µl, 40µl, 60µl, 80µl and 100µl) and different temperature set during film forming solution (70°C , 75°C, 80°C, 85°C and 90°C) on film’s solubility and their mechanical properties. This study also been performed to develop biodegradable film from natural resources such as gelatin and starch and incorporated them with essential turmeric oil. The materials and method that have been used in this study were gelatin from white mouse, tapioca starch, pure glycerol and film forming solution methodology. Analysis that have been done were solubility test and mechanical properties test. Basically for film forming solution, the ratio of gelatin to starch that have been used was 2:3. Based on the solubility test we can concluded that the larger the turmeric oil’s volume been used in film preparation process, the larger values of solubility percentage or film’s weight loss. Same trend can be seen if we increase the temperature during film preparation of film forming solution processes. Different batch was prepared under different temperatures and based on the result we can concluded that, higher temperature resulted in increases in film’s solubility.